2009
DOI: 10.1111/j.1463-1326.2008.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipohypertrophy: does it matter in daily life? A study using a continuous glucose monitoring system

Abstract: The pharmacokinetic and pharmacodynamic effect of injecting into lipohypertrophic tissue is small in comparison to the usual clinical variation observed with insulin injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…It was concluded by Overland J, et al, [8] that "the pharmacokinetic and pharmacodynamic effect of injecting into lipohypertrophic tissue is small in comparison to the usual clinical variation observed with insulin injections as there was no difference in continuous glucose monitoring (CGMS) profiles between areas with lipohypertrophy and areas without lipohypertrophy. Therefore, the exact effect of lipohypertrophy is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded by Overland J, et al, [8] that "the pharmacokinetic and pharmacodynamic effect of injecting into lipohypertrophic tissue is small in comparison to the usual clinical variation observed with insulin injections as there was no difference in continuous glucose monitoring (CGMS) profiles between areas with lipohypertrophy and areas without lipohypertrophy. Therefore, the exact effect of lipohypertrophy is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…[7] LH retards insulin absorption significantly and to a sufficient magnitude to have an adverse effect on diabetes control. [8] Proper rotation of injection site and avoidance of needle reuse can prevent LH, or reduce its size which in turn improves glucose control. [4]…”
Section: Introductionmentioning
confidence: 99%
“…Blanco et al (4) observed significantly higher insulin dosing in patients with, versus those without, LHT, but did not report A1C levels. On the other hand, no differences were found in diabetes control or insulin demands between patients with and without LHT in one cross-sectional study (2), and an outpatient 3-day study with continuous glucose monitoring failed to show any substantial differences in insulin pharmacokinetics (PK) and BG profiles (7), so those authors felt it unnecessary to advise patients to avoid LHT for insulin injections. In addition, two meal studies with pharmacodynamic (PD) and PK comparisons of insulin injection into LHT versus normal adipose tissue (NAT) showed inconsistent results.…”
mentioning
confidence: 96%